MICRO SCALE KIT MEDIA DEVELOPMENT BASED ON 5E INSTRUCTIONAL MODEL TO PRACTICE STUDENTS SCIENCE PROCESS SKILLS GRADE XI HIGHER SCHOOL ON THERMOCHEMISTRY MAIN SUBJECT (Universitas Negeri Surabaya, 2017)
Practical activities are a part that cannot be separated from chemistry learning. To maintain the performance of chemistry learning through practical, micro-scale kit media was developed to help the practical implementation in the classroom. Therefore, this research aims is to develop a kit which is valid, practice, and effective. This type of research used development refers to methods of Research and Development (R&D) Borg and Gall. Kit that have been reviewed and validated then tested on 12 students of eleventh grade senior high school. The results showed that the Kit feasibility based on validity content and construct with an average percentage 89.63% include very appropriate category. Kit feasibility based on practicality aspects in terms of student responses obtained percentage between 91.67%-100% include very practical category. Kit feasibility based on aspects of effectiveness obtained from the posttest students science process skills with improving N-gain indicated that 91.67% of students completed with gain score 75% of students included in high category and 25% of students include in enough category. It can be concluded that the micro-scale Kit media based on 5E Instructional Model to practice student’s science process skills feasible based on the aspect of validity, practicality, and effectiveness Key Word: Kit Media, 5E Instructional Model, Science Process Skill